Société, cinéma et ingénieries relationnelles - Olivier Fournout (Communication)
Film narratives are often used to illustrate management concepts. Selected excerpts serve as examples of how human beings relate to one another. From his case study, the author attempts to identify the reasons that could justify such pedagogical and training practices. He then reflects upon the question of how cinema can mediate the establishment of socialized practices in a professional environment. He finally suggests that the configuration of the American cinematic hero and of the leader in management literature both share a set of ethical and behavioural requirements.